Landscape of Globally Minded Leadership Development for Public Servants - Ito Tsumagari, Maki (Policy & Governance Review, 2025)
This study aimed to unravel how far the concept of leadership development for agility has gone into the curriculum of higher education institutions (HEI) as an indication of their preparedness for educating public servants in the volatile, uncertain, complex, and ambiguous (VUCA) policy environment of today. A qualitative, systematic analytical method was adopted by referencing the public policy and administration schools of the world's top 100 ranked universities in The Times Higher Education World University Overall Rankings 2024. The results were categorized into three executive programs with the potential for leadership enhancement through customized arrangements, two executive programs with the label of "leadership," and one executive program that specifically addresses agility-relevant leadership development for the VUCA era. The study concluded that leadership development focusing on agility is still at an infancy/early stage of adoption by the world's public policy and administration schools. This study made a step forward by identifying where the programs are already running, down to the point where the university is running, and which public policy and administration programs. The practical implications of the study reside in its referential value for those governments and/or their professionals in identifying where services are provided.